2010
DOI: 10.1007/s12291-010-0063-5
|View full text |Cite
|
Sign up to set email alerts
|

Leucine125Valine (Leu125Val) Gene Polymorphism of Platelet Endothelial Cell Adhesion Molecule-1 (PECAM-1) and Myocardial Infarction in Indian Population

Abstract: Platelet-endothelial cell adhesion molecule-1 (PECAM-1) has role in atherosclerotic plaque development as well as in thrombosis leading to myocardial infarction (MI). Present study was aimed to analyse the association of PECAM-1 Leu125Val gene polymorphism with MI in Indian population. Subjects included healthy individuals as control (N = 116) and MI patients (N = 100) divided into two groups; MI patients at presentation of the acute event (MI-Group-1, N = 46) and patients with recent event of MI stabilized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Previous studies reported that PECAM-1 polymorphisms have been associated with coronary artery stenosis or atherosclerosis [ 23 25 ]. Three common polymorphisms (Leu125Val, Asn563Ser, and Gly670Arg) located on the PECAM-1 gene have been verified to be in association with these diseases [ 8 , 24 , 26 ]. And it found that +373 C/G (Leul25Val) polymorphism is associated with cerebral infarction or myocardial infarction [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that PECAM-1 polymorphisms have been associated with coronary artery stenosis or atherosclerosis [ 23 25 ]. Three common polymorphisms (Leu125Val, Asn563Ser, and Gly670Arg) located on the PECAM-1 gene have been verified to be in association with these diseases [ 8 , 24 , 26 ]. And it found that +373 C/G (Leul25Val) polymorphism is associated with cerebral infarction or myocardial infarction [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three common polymorphisms (Leu125Val, Asn563Ser, and Gly670Arg) located on the PECAM-1 gene have been verified to be in association with these diseases [ 8 , 24 , 26 ]. And it found that +373 C/G (Leul25Val) polymorphism is associated with cerebral infarction or myocardial infarction [ 26 , 27 ]. PECAM-1 gene +373 C/G (Leul25Val) mutation position is in Exon-3 encoding first-extracellular Ig-like domain [ 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an association between the rs668 PECAM-1 gene and either the increased levels of soluble PECAM-1 or ischemic stroke was found in the Chinese population [ 21 ]. An association between the rs668 PECAM-1 gene and increased levels of soluble PECAM-1 was confirmed in the setting of patients with acute MI [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD31/PECAM-1 mediates cell migration by regulating integrins and stimulates integrin activation. 19 , 20 Some studies have found that polymorphisms of CD31/PECAM-1 are associated with several diseases such as myocardial infarction or acute coronary syndrome, bronchial asthma, and severe malaria; 12 15 , 21 23 however, studies to date seldom focus on cerebral infarction risk. Asn563Ser is a polymorphism that is located on exon 8 at codon 563 of the CD31/PECAM-1 gene and it leads to a change from an asparagine to a serine.…”
Section: Discussionmentioning
confidence: 99%
“… 11 These CD31/PECAM-1 polymorphisms have been deemed to be associated with myocardial infarction or coronary artery disease (CAD). 12 15 However, only one study 16 to date has focused on the relationship between CD31/PECAM-1 polymorphisms and cerebral infarction, and it found that Leu125Val polymorphism and plasma sPECAM-1 levels are associated with cerebral infarction.…”
Section: Introductionmentioning
confidence: 99%